THE UNIFIED PATENT COURT – A NEW JUDICIAL BODY FOR THE SETTLEMNT OF PATENT DISPUTES WITHIN THE EUROPEAN UNION - Ćeranić, Jelena (EU and comparative law issues and challenges series (ECLIC), 2018)
The Unified Patent Court is established by the Agreement on Unified Patent Court, signed in February 2013 by twenty five EU Member States. The Agreement will enter into force after the ratification of thirteen Member States, including France, Germany and United Kingdom. The Unified Patent Court is a judicial body for the settlement of disputes relating to the European Patents and European Patents with unitary effect. European patent means a patent granted under the provisions of the European Patent Convention (EPC), which does not benefit from unitary effect by the virtue of Regulation (EU) No 1257/2012 of the European Parliament and of the Council of 17 December 2012 implementing enhanced cooperation in the area of the creation of the unitary patent protection. European patent with unitary effect means a patent granted under the provisions of the EPC which benefits from unitary effect by the virtue of Regulation (EU) No 1257/2012. Taking into consideration a number of attempts to create a unified patent protection system within the EU, the first part of the article represents an overview to the history of establishment of the unified patent litigation system. The second part analyses legal bases, sources of law and structure of the Unified Patent Court. The special attention is devoted to the relation between the Unified Patent Court and the European Court of Justice. In the third part, the author examines challenges that will face the users of the new court for the settlement of disputes relating to the European Patents and European Patents with unitary effect.